Infusion of Strychnos lucida as an Alternative Therapy for Malaria Treatment: An In Vivo Study in Plasmodium berghei-Infected Mice (Mus musculus) - Meillisa Carlen Mainassy; Abdul M. Ukratalo (Jurnal Penelitian Pendidikan IPA, 2025)
Malaria drug resistance results in severe symptoms and treatment failure. In an effort to develop new medications, screening of several plants with potential antimalarial properties has been conducted. Strychnos lucida is known to contain various active compounds such as alkaloids and tannins, which may exhibit antimalarial properties. This study aims to determine the potential of Strychnos lucida infusion as an alternative therapy for malaria treatment. This research was experimental, employing a completely randomized design. A total of 20 mice were divided into 5 groups: a negative control group (mice infected with Plasmodium berghei without treatment), a positive control group (mice infected with Plasmodium berghei and treated with quinine tablet malaria drug), and three experimental groups of mice infected with Plasmodium berghei and treated with Strychnos lucida infusions at doses of 1.5g/200 ml, 3g/200 ml, and 6g/200 ml, administered at a volume of 0.52 ml per mouse per day. The treatments were given for 4 consecutive days with observations continuing until the 6th day. The results were analyzed using two-way ANOVA. The findings indicate that the Strychnos lucida infusion inhibited the growth of Plasmodium berghei in vivo, suggesting antimalarial activity of the plant in the biological system of infected mice.